Intergenerational programming of impaired nephrogenesis and hypertension in rats following maternal protein restriction during pregnancy. - Harrison, Matthew James (2009)
Epidemiological associations between birthweight and cardiovascular disease in adult life are supported by rodent experiments showing that undernutrition in fetal life programmes adult blood pressure. In rats, the feeding of a maternal low protein(MLP) diet during gestation programmes hypertension. Given interest in the mechanistic role of epigenetic modification of gene expression in programming, this study aimed to assess the potential for a nutritional insult to impact across several generations. Pregnant female Wistar (F0) rats were fed a control (n=10) or MLP diet(n=10) throughout gestation. At delivery all animals were fed the same standard laboratory chow diet. At approximately 10 weeks of age, F1 generation offspring were mated to produce a second generation (F2) without any further dietary change. The same procedure was adhered to, to produce the F3 generation. Physiological analysis confirmed F1 generation MLP exposed offspring exhibited raised (P<0.001)systolic blood pressure and reduced nephron number (P<0.001) compared with controls. Raised blood pressure and reduced nephron number were also noted in the F2 generation (P<0.001) and this intergenerational transmission occurred via both the maternal and paternal lines, No effect was noted in the F3 generation. Microarray analysis highlighted a number of genes that were differentially expressed however upon RT-PCR analysis results were not significant. DNA methylation analysis noted in a trend towards hypomethylation in MLP exposed rats and their offspring as described in previous studies. In conclusion, data within this thesis shows for the first time, that fetal protein restriction may play a critical role in determining blood pressure and overall disease risk in a subsequent generation. It is clear from the data that both males and females can transmit their phenotype to a subsequent generation. This finding suggests that maternal diet can influence the nature of epigenetic markers in germ line cells.